2023
DOI: 10.1002/rra.4109
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying floodplain heterogeneity with field observation, remote sensing, and landscape ecology: Methods and metrics

Abstract: Floodplains provide numerous ecosystem services that depend on the spatial heterogeneity, or patchiness, of the floodplain. Direct and indirect human alterations of rivers can reduce floodplain heterogeneity and function, but relatively little is known of patterns of floodplain heterogeneity in natural, fully functional floodplains. We quantify floodplain heterogeneity at four sites in the United States with the objectives of (i) developing a method of combining field measurements and remote sensing data produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…Patch were delineated along the floodplain transects on the 3-10 m scale and their boundaries were collected with a Garmin GPSMAP 66ST handheld GPS (±3 m horizontal accuracy). Field classifications for specific sites can be found in Table S1 in Supporting Information S1, Iskin and Wohl (2023b), Table 3, and Iskin (2023), Table 3.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patch were delineated along the floodplain transects on the 3-10 m scale and their boundaries were collected with a Garmin GPSMAP 66ST handheld GPS (±3 m horizontal accuracy). Field classifications for specific sites can be found in Table S1 in Supporting Information S1, Iskin and Wohl (2023b), Table 3, and Iskin (2023), Table 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…Floodplain boundaries were delineated manually in ArcGIS Pro using field transect data, Sentinel imagery, DEMs, and national park boundaries (where applicable). A 10-m geodesic buffer was added to the floodplains to account for field and/or user error (Iskin & Wohl, 2023b). Additional specifics on floodplain delineation can be found in Text S2 in Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have identified correlations between topographic heterogeneity and habitat suitability (Bellmore & Baxter, 2014; Stoffers et al., 2022), increased biodiversity (Morán‐Ordóñez et al., 2015), and attenuation of biogeochemical fluxes (Gooseff et al., 2007; Westbrook et al., 2006). Because of this noted importance of topographic heterogeneity, many tools and metrics have been developed to quantify the distribution of physical elements, organization of patterns, or the variation of shapes of discretely classified patches (Dietrich et al., 2005; Iskin & Wohl, 2023; Nelson et al., 2014; Scott et al., 2022; Scown et al., 2015; Wohl, 2016a). These metrics have been used to inform design goals and measures of river restoration success (Hinshaw et al., 2022; Scott et al., 2022), and the physical processes that drive them have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This may provide a fundamental approach to comparing channel forms of all types. Geomorphic form variety may also support decision-making processes as a tool for river restoration planning and design, particularly when geomorphic complexity enhancement is a design objective and may complement quantitative spatial heterogeneity metrics often applied for ecological research (Iskin & Wohl, 2023). Example project objectives may include better understanding of hydrodynamic processes (Wyrick et al, 2014), modelling ecological patterns (Dilts et al, 2023) or understanding the impacts of stormwater runoff (Walsh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%